Strategi Inovatif Pemanfaatan Teks Proposal untuk Meningkatkan Hasil Belajar Bahasa Indonesia di Sekolah Dasar 101961 - Santa Emelia Sitorus; Febbita Putri Amanda Alwi Geovany; Febry Nurhayati Br Sagala; Hendra Kurnia Pulungan (Universitas Palan, 2024)
The proposal text is one of the text types taught in Indonesian language learning in elementary schools. However, the teaching of proposal texts is often carried out using conventional methods that do not actively involve students. This research aims to explore innovative strategies in utilizing proposal texts to improve Indonesian language learning outcomes for elementary school students. The research method used is classroom action research by applying a project-based learning strategy through group assignments to develop proposal texts. The research subjects were fifth-grade students at Public Elementary School X in City Y. Data were collected through observations, written tests, and interviews with teachers and students. The research results show that innovative strategies for using proposal texts can improve student learning outcomes, including writing skills, understanding of text structure, and vocabulary and language elements. Students become more motivated and actively involved in the learning process. They also develop critical thinking, creativity, and collaboration skills in developing proposal texts. This strategy has proven effective and can be implemented in Indonesian language learning in other elementary schools to improve student learning outcomes and language skills.